Determining The Center of Composition, Balance and Proportion (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
In mastering and deeper study of the art of composition, the composition center, balance and proportion are defined, and the sequence of work is highlighted. The concepts of center, balance, and proportion are foundational principles in the fields of art, architecture, and visual design. This paper explores methodologies for identifying the center of composition, evaluating balance—both symmetrical and asymmetrical—and achieving visual proportion in artistic and architectural works. By examining classical theories, modern digital techniques, and case studies from both historical and contemporary visual arts, the study aims to offer a comprehensive understanding of how these elements interact to guide visual perception and enhance aesthetic value.